Strategi Penanganan Perdagangan Manusia di Wilayah Perbatasan Indonesia - Malaysia - Erika Mayasari; Herlina J.R Saragih; Edy Saptono (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study examines strategies for addressing human trafficking in the Indonesia-Malaysia border region using qualitative methods through a literature review using a SWOT analysis. Sources include books, scientific journals, articles, research reports, undergraduate theses, dissertations, and various other sources. This is believed to be a contributing factor to the high rate of human trafficking in the border region, such as weak supervision, limited public understanding of the law, and limited infrastructure and coordination between institutions on the Indonesia-Malaysia border. Human trafficking is defined as "the recruitment, transportation, transfer, harboring, or receipt of persons by means of the threat or use of force or other forms of coercion, of abduction, of fraud, of deception, of the abuse of power or of a position of vulnerability, or of the giving or receiving of payments or benefits to achieve the consent of a person having control over another person, for the purpose of exploitation." (UNODC, 2024). This literature review concludes that addressing human trafficking requires sustained multi-sectoral synergy to create effective protection and prevention. This study recommends regulatory reform, public education, and improved technological surveillance to minimize the risk of human trafficking in the Indonesia-Malaysia border region.